2019
DOI: 10.1002/jia2.25269
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability, perceived reliability and challenges associated with distributing HIV self‐test kits to young MSM in Uganda: a qualitative study

Abstract: Introduction HIV self‐testing is a flexible, accessible and acceptable emerging technology with a particular potential to identify people living with HIV who are reluctant to interact with conventional HIV testing approaches. We assessed the acceptability, perceived reliability and challenges associated with distributing HIV self‐test (HIVST) to young men who have sex with men (MSM) in Uganda. Methods Between February and May, 2018, we enrolled 74 MSM aged ≥18 years purposively sampled and verbally consented t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 25 publications
5
51
0
Order By: Relevance
“…HIV testing is the entry point to HIV care; increasing testing coverage is a key step to reaching the first UNAIDS 90-90-90 target, i.e., 90% of people living with HIV knowing their HIV status. However, testing uptake is still low among MSM despite efforts to scale up prevention services for key populations (KP) in Uganda [5][6][7][8]. A recent bio-behavioral survey of Ugandan MSM found that 35% had never tested for HIV [6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…HIV testing is the entry point to HIV care; increasing testing coverage is a key step to reaching the first UNAIDS 90-90-90 target, i.e., 90% of people living with HIV knowing their HIV status. However, testing uptake is still low among MSM despite efforts to scale up prevention services for key populations (KP) in Uganda [5][6][7][8]. A recent bio-behavioral survey of Ugandan MSM found that 35% had never tested for HIV [6].…”
Section: Introductionmentioning
confidence: 99%
“…A recent bio-behavioral survey of Ugandan MSM found that 35% had never tested for HIV [6]. HIV self-testing (HIVST), in which an individual performs and interprets his/her own HIV test [8][9][10][11][12][13], is an acceptable and innovative approach that could increase knowledge of HIV sero-status among MSM, and is recommended by the World Health Organization and Uganda Ministry of Health [3,[14][15][16][17][18][19][20][21][22]. In addition, HIVST is convenient since individuals can test at any time, in private, without having to present to a clinic during fixed working hours.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, both behavioral and structural interventions are of paramount importance and the participatory engagement of youth in the design and implementation of programming for a targeted response cannot be ignored (2,24,38,(40)(41)(42). UNAIDS outlines the importance of capacity building initiatives of youth-led organizations and associations to ensure their ability to mobilize and advocate for their peers (3).…”
Section: Discussionmentioning
confidence: 99%
“…Although these studies have accessed HIVST acceptability by MSM, few have explored how previous testing experiences differs in its associated factors with acceptability, especially among those who were never tested as compared to those who had a previous HIV negative result. Both groups could potentially bene t from access to additional testing services [36]. Moreover, there are no studies of HIVST acceptability among a large population sample of Brazilian MSM.…”
Section: Introductionmentioning
confidence: 99%